Valvular and ascending aortic hemodynamics of the On-X aortic valved conduit by same-day echocardiography and 4D flow MRI - Lee, Jeesoo; Huh, Hyungkyu; Scott, Michael B.; Elbaz, Mohammed S. M.; Puthumana, Jyothy J.; McCarthy, Patrick; Malaisrie, S. Christopher; Markl, Michael; Thomas, James D.; Barker, Alex J. (Frontiers in Cardiovascular Medicine, 2023)
This study aims to assess whether the On-X aortic valved conduit better restores normal valvular and ascending aortic hemodynamics than other commonly used bileaflet mechanical valved conduit prostheses from St. Jude Medical and Carbomedics by using same-day transthoracic echocardiography (TTE) and 4D flow magnetic resonance imaging (MRI) examinations. TTE and 4D flow MRI were performed back-to-back in 10 patients with On-X, six patients with St. Jude (two) and Carbomedics (four) prostheses, and 36 healthy volunteers. TTE evaluated valvular hemodynamic parameters: transvalvular peak velocity (TPV), mean and peak transvalvular pressure gradient (TPG), and effective orifice area (EOA). 4D flow MRI evaluated the peak systolic 3D viscous energy loss rate (VELR) density and mean vorticity magnitude in the ascending aorta (AAo). While higher TPV and mean and peak TPG were recorded in all patients compared to healthy subjects, the values in On-X patients were closer to those in healthy subjects (TPV 1.9 ± 0.3 vs. 2.2 ± 0.3 vs. 1.2 ± 0.2 m/s, mean TPG 7.4 ± 1.9 vs. 9.2 ± 2.3 vs. 3.1 ± 0.9 mmHg, peak TPG 15.3 ± 5.2 vs. 18.9 ± 5.2 vs. 6.1 ± 1.8 mmHg, p < 0.001). Likewise, while higher VELR density and mean vorticity magnitude were recorded in all patients than in healthy subjects, the values in On-X patients were closer to those in healthy subjects (VELR: 50.6 ± 20.1 vs. 89.8 ± 35.2 vs. 21.4 ± 9.2 W/m3, p < 0.001) and vorticity (147.6 ± 30.0 vs. 191.2 ± 26.0 vs. 84.6 ± 20.5 s-1, p < 0.001). This study demonstrates that the On-X aortic valved conduit may produce less aberrant hemodynamics in the AAo while maintaining similar valvular hemodynamics to St. Jude Medical and Carbomedics alternatives.